Measuring down-side risk-realised semivariance. - Barndorff-Nielsen, O; Kinnebrock, S; Shephard, N (Oxford-Man Institute of Quantitative Finance, 2008)
We propose a new measure of risk, based entirely on downwards moves measured using high frequency data. Realised semivariances are shown ato have important predictive qualitites for future market volatility. The theory of these new measures is spelt out, drawing on some new results from probability theory.